The interactive teaching of students used at the department of pediatrics - Lezhenko, G. O.; Pashkova, O. E.; Lebedynets, O. M.; Sidorova, I. V.; Kraynya, H. V.; Леженко, Геннадій Олександрович; Пашкова, Олена Єгорівна; Лебединець, Олександра Миколаївна; Сидорова, Ірина Володимирівна; Крайня, Ганна Вікторівна (Czech Republic, Karlovy Vary: Skleněný Můstek, 2017)
The educational process in institutions of higher medical education should be oriented towards the use of modern information technologies . Among the new technologies in education, since 2012, mass open online courses have spread around the world, such as a combination of free video lectures, interactive tasks and forums for discussing teaching materials. However, only online education is impossible in medicine, and requires practical and clinical experience, working directly in the clinic with patients such as mixed education.